2014
DOI: 10.1186/2046-4053-3-56
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of computerized order entry at reducing preventable adverse drug events and medication errors in hospital settings: a systematic review and meta-analysis

Abstract: BackgroundThe Health Information Technology for Economic and Clinical Health (HITECH) Act subsidizes implementation by hospitals of electronic health records with computerized provider order entry (CPOE), which may reduce patient injuries caused by medication errors (preventable adverse drug events, pADEs). Effects on pADEs have not been rigorously quantified, and effects on medication errors have been variable. The objectives of this analysis were to assess the effectiveness of CPOE at reducing pADEs in hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(198 citation statements)
references
References 66 publications
5
179
1
6
Order By: Relevance
“…Respondents reported minimal use of technologies (Scale: 1.0), which serve as enabling tools in facilitating dispensing activities and minimizing errors. Researchers have shown that electronic health records (EHR), computerized prescription order entry (CPOE) technologies and e-pharmacy are very beneficial in error and cost minimization, dispensing high-alert medications, and improved patient outcomes; [39][40][41][42] while some reports show mixed benefits. [26,43] These technologies if made available in our practice setting would minimize errors and uncertainty, and enhance quality of care to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Respondents reported minimal use of technologies (Scale: 1.0), which serve as enabling tools in facilitating dispensing activities and minimizing errors. Researchers have shown that electronic health records (EHR), computerized prescription order entry (CPOE) technologies and e-pharmacy are very beneficial in error and cost minimization, dispensing high-alert medications, and improved patient outcomes; [39][40][41][42] while some reports show mixed benefits. [26,43] These technologies if made available in our practice setting would minimize errors and uncertainty, and enhance quality of care to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Even if CPOE systems induce adverse events [31], the controversy about the overall helpful or harmful effect of CPOE [32] is now behind us [2][33] as CPOE implementation is now mandatory in France [34]. Stavri and Ash [13] suggested that success is often preceded by failure.…”
Section: Cpoe Was Never Perceived As Superior To Pboe Qualitative Anmentioning
confidence: 99%
“…In theory, CPOE allows a reduction in duplicate medications, drug overdoses, contraindications, unconsidered allergies, etc [1]. In practice, it reduces preventable adverse drug events [2]. While implementation of CPOE in hospitals in the USA [3] [4] and in the Netherlands seems to be well underway, other countries lag far behind [5].…”
Section: Introductionmentioning
confidence: 99%
“…Under this act, hospitals would obtain financial incentives if they used information technology (e.g., electronic health records) to improve quality, safety and efficiency of healthcare while engaging patients and their families in care. [40][41][42] The HITECH Act worked as a regulatory, technological and…”
Section: Technological Environmentmentioning
confidence: 99%